One Water - McCue, Robert, 1966- (Book collections on Project MUSE., 2018)
"In One Water the author takes us on a journey through the Alaskan wilderness to the streets of its second largest city in a quest to find meaning in this world. The book is not merely a narrative of his adventures but also describes many of the geological, biological, and climactic circumstances that have shaped this great land. Another strand woven through this collection is the coming of age story of a freewheeling young drifter slowly accepting his transformation to adulthood (or close to it, anyway) and his role as a member of a family"--Provided by publisher.